Secondary succession of mixed plantations established to rehabilitate abandoned pasture in the Peruvian Amazon - Kobayashi, Shigeo (2014)
Secondary succession or facilitation processes carried out at sites established for rehabilitating abandoned pastures and degraded forests (prurmas) are instrumental in their return to original forest status. An understanding of these secondary succession processes contributes to the rehabilitation of degraded forest ecosystems and to the livelihoods of local communities, and aids in conserving biodiversity. We studied secondary succession in mixed species plantations that were established to rehabilitate abandoned land. The initial vegetation in these abandoned pastures and croplands was grassland composed of three dominant species: Rottboellia exaltata, Imperata brasiliensis, and Brachyaria decumbens. After tree planting and weeding had been carried out, the site was first invaded by R. exaltata and Baccharis floribunda. These two species, which depend solely on sexual and not vegetative reproduction, facilitated secondary succession and elevated species diversity by enabling subsequent invasion by several species. By contrast, B. decumbens, I. brasiliensis, and Hyparrhenia rufa depend mainly on vegetative reproduction involving rhizomes and tillers, and subsequent invasion by other species was relatively less in stand types dominated by these three species. We found that further adequate rehabilitation techniques were necessary for the respective vegetation types.